Akuntansi Dalam Pencapaian Tujuan Rumah Tangga Islami - Dwiya Endah Pandu Probowati (Institute of Research and Community Service at Islamic University of Bunga Bangsa Cirebon, 2021)
As stated by Allah in Surah Al Baqarah 282, Islam views accounting as a mandate that must be carried out in muamalah activities. From a scientific point of view, accounting is a science, art and technique of financial recording of business entities which includes the process of recording, journaling, and reporting. In a business entity, accounting is a tool that can help achieve the goals of a business entity, namely profit, accounting provides financial report output that can be a source of information related to the performance of business entity managers, seeing profitability and business performance trends from period to period and so on. In general, the use of accounting will simplify the accountability process, assist in performance appraisal and facilitate the achievement of business entity objectives. The household is the smallest social entity that has a goal, in Islam the goal of the household is to achieve sakinah mawaddah and wa rokhmah, in order to achieve this goal, special well-planned steps are needed. In household accounting plays a very important role in the process of recognizing what household resources are, budgeting household needs both in the short and long term, further accounting also helps implementers of household activities to see the realization and household budgets. This research is a qualitative research using library research method. In this study, the researcher revealed the important role of accounting for the achievement of household goals in an Islamic economic perspective. The purpose of this study is to provide an understanding of